The Influence of Customer Reviews , Customer Ratings , Price Perceptions on Fresh Perfume Purchase Decisions on the Shopee Marketplace - Zakiyatuzzulfa, Zakiyatuzzulfa; Subagyo, Subagyo (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This research aimed to analyze the impact of customer reviews, ratings, and price perceptions on purchasing decisions for Fresh perfume on the Shopee marketplace, both individually and collectively. Design/Methode/Approach : This study utilizes a quantitative research approach with a causal research design, aiming to examine cause-and-effect relationships between variables. The research population comprises students enrolled in the Faculty of Economics and Business at Universitas Nusantara PGRI Kediri who have purchased Fresh perfume through Shopee. A sample of 40 respondents was selected using purposive sampling. The process of data analysis in this study was carried out using the multiple linear regression method. This statistical technique was employed to assess and measure the extent to which customer reviews, customer ratings, and consumers' perceptions of price influence their purchasing decisions. Research Finding : The study results show that customer reviews significantly influence purchasing decisions, whereas customer ratings and price perceptions do not. However, all three variables collectively impact purchasing decisions. Theoretical contribution/Originality : This research contributes to understanding the factors that affect consumer purchasing decisions on Shopee, particularly for Fresh perfume products. Practitionel/Policy implication : This research offers valuable marketing strategy insights for companies, particularly in managing customer reviews, ratings, and pricing to enhance purchasing decisions on Shopee. Research limitation : This research is limited to three independent variables, leaving the possibility that other unmeasured factors also affect purchasing decisions.